1997
DOI: 10.1177/096914139700400109
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Cystic Fibrosis in the Trent Region (UK): Two-Stage Immunoreactive Trypsin Screening Compared with a Three-Stage Protocol with DNA Analysis as an Intermediate Step

Abstract: Objectives— To assess neonatal screening for cystic fibrosis using immunoreactive trypsin, either alone or in conjunction with DNA analysis for the AF508 mutation. A novel three-stage screening protocol was compared with the previously introduced two-stage immunoreactive trypsin-DNA protocol. Design— (a) Collection of data from a 41/2 year period (phase 1) of two-stage immunoreactive trypsin screening. The initial dried blood samples were obtained at 6 days of age and repeat samples at 27 days of age from babi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
(8 reference statements)
1
19
0
2
Order By: Relevance
“…While research in relation to newborn CF screening may suggest little evidence of enduring adverse psychosocial effects, 7,59,73 parents may be distressed or depressed during the process of newborn screening, 14,60,[74][75][76][77][78][79][80] which may relate to difficulties in understanding relatively complex information. 15,58 Health professional communication may also shape parents responses to newborn CF screening results, 81 which can include shock and anxiety, 14,58,59,82,83 with health professional communication following newborn carrier identification sometimes found wanting by parents in relation to both CF and SC.…”
Section: Anxiety and Understanding Following Carrier Resultsmentioning
confidence: 99%
“…While research in relation to newborn CF screening may suggest little evidence of enduring adverse psychosocial effects, 7,59,73 parents may be distressed or depressed during the process of newborn screening, 14,60,[74][75][76][77][78][79][80] which may relate to difficulties in understanding relatively complex information. 15,58 Health professional communication may also shape parents responses to newborn CF screening results, 81 which can include shock and anxiety, 14,58,59,82,83 with health professional communication following newborn carrier identification sometimes found wanting by parents in relation to both CF and SC.…”
Section: Anxiety and Understanding Following Carrier Resultsmentioning
confidence: 99%
“…It is envisaged that the proposed screening programme will be based on a three-stage protocol. 6 In Table 4 but not in the 31 mutation panel; 1154insTC, E60X, P67L, Y569D, L218X, 1161delC and R709X. the first stage, a confirmed raised immunoreactive trypsinogen (IRT) level on a day 4 -6 blood spot sample would be followed by a second stage DNA analysis for CFTR mutations from the same blood spot card.…”
Section: Discussionmentioning
confidence: 99%
“…Pollitt et al 44 , using this methodology, observed a reduction of 92% in the number of recalls for a second IRT test, as compared to the IRT/IRT protocol, and a reduction of 80% in recalls for the sweat test.…”
Section: Currently Used Protocols • Irt/irtmentioning
confidence: 99%
“…Pancreatitis-associated protein (PAP) is elevated in the blood of children with cystic fibrosis 44 . Sarles et al 45 studied the combined use of measuring PAP and IRT.…”
Section: Other Approaches • Pap/irtmentioning
confidence: 99%
See 1 more Smart Citation